Right ventricular mural infective endocarditis after traumatic tricuspid valve regurgitation in a 40-year-old man: A case report. Issue 2 (February 2023) - Matsuzoe, Hiroki; Sato, Shunsuke; Nishio, Ryo; Ozawa, Makito; Matsumoto, Daisuke; Takaishi, Hiroshi
Abstract: As the clinical manifestations of traumatic tricuspid valve regurgitation vary according to the extent of tricuspid valve injury, this condition can often go unnoticed and be incidentally discovered. Here, we report the case of a 40-year-old man with patent foramen ovale, in which severe tricuspid regurgitation due to tricuspid valve prolapse was incidentally discovered following blunt chest trauma. Further examination revealed that the prolapse had also caused active right ventricular mural infective endocarditis. The patient had no relevant past medical history of chronic debilitating disease or immunosuppression. After evaluation by the cardiology team, emergent surgical tricuspid valvular repair was successfully performed. Learning objective: Tricuspid valve prolapses resulting from chest trauma may occasionally lead to severe tricuspid regurgitation. Furthermore, this may cause active right ventricular infective endocarditis. In the present case, Staphylococcus aureus was detected in blood cultures, which is usually rapidly progressive and often leads to devastating consequences. Early surgical approach should be considered in cases of infection in the left atrium via patent foramen ovale.